Phase I Study of Cisplatin, Hyperthermia, and Lapatinib in Patients With Recurrent Carcinoma of the Uterine Cervix in a Previously Irradiated Area. (6th February 2015) - van Meerten, Esther; Franckena, Martine; Wiemer, Erik; van Doorn, Lena; Kraan, Jaco; Westermann, Anneke; Sleijfer, Stefan
Abstract : Background: Patients with recurrent cervical cancer in a previously irradiated area might benefit from cisplatin combined with hyperthermia. Lapatinib inhibits the intracellular tyrosine kinase domain of the epidermal growth factor receptor (EGFR) and HER2. Overexpression of EGFR and HER2 is frequently seen in patients with cervical cancer and is potentially involved in chemotherapy resistance. In addition, preclinical data suggest a synergistic effect of combining cisplatin and lapatinib. Consequently, this phase I dose‐escalation study was performed to determine the maximum tolerated dose (MTD) of lapatinib added to fixed doses of cisplatin and hyperthermia. Methods: Eight patients with previously irradiated recurrent cervical carcinoma were enrolled and scheduled for 6 weekly administrations of 70 mg/m 2 cisplatin combined with locoregional hyperthermia. Hyperthermia consisted of the achievement of intraluminal temperatures of 40–43°C as homogeneously as possible over 60 minutes. Daily lapatinib was added on days 1–56, starting with a dose level of 1, 000 mg. The MTD was defined as the highest dose at which ≤1 of 6 patients experienced dose‐limiting toxicity (DLT). DLT was defined as grade 4 neutropenia lasting >7 days, febrile neutropenia grade ≥3, grade 4 thrombocytopenia, grade ≥2 renal toxicity, postponement of cisplatin and hyperthermia for ≥2 weeks, or grade ≥3 nonhematologic adverse events except for nausea or vomiting, diarrhea, or skin toxicity, for which the following DLT definitions were applied: grade ≥3 persistent nausea or vomiting or diarrhea despite optimal medical treatment or grade 4 skin toxicity. Safety, pharmacodynamics, and response were assessed. Results: The first two patients of both the 1, 000‐ and 750‐mg dose level experienced DLTs. Of the four patients treated at dose level −2 (500 mg), only one patient was able to complete the treatment as planned, two patients experienced a DLT, and one patient was not evaluable because of early progressive disease. In the evaluable patients, one patient with progressive disease, four patients with stable disease, and two patients with partial response were observed. One patient with a partial response had a resection of the local recurrence. Pathological analysis showed a complete pathological response. Enumeration of circulating endothelial cells measured at baseline and during therapy did not show consistent results. The same applied for the pharmacodynamic effects on Ki‐67, p27Kip1, and EGFR in pretreatment and on‐therapy skin biopsies. Conclusion: It is not feasible to combine lapatinib with fixed doses of cisplatin and hyperthermia in patients with recurrent cervical carcinoma in a previously irradiated area mainly because of increased cisplatin‐related toxicity. The observed complete pathological response is intriguing and warrants further investigation of combinations consisting of HER2 blockade and cisplatin plus hyperthermia. Abstract : 摘要 背景 . 既往照射野内复发子宫颈癌患者可能从顺铂联合热疗获益。拉帕替尼可抑制细胞内表皮生长因子受体（EGFR）和HER2的酪氨酸激酶域。EGFR和HER2过表达常见于子宫颈癌患者，而且在化疗耐药中也可能涉及到。此外，临床前数据提示顺铂与拉帕替尼联合具有协同作用。因此我们开展了这项I期剂量递增研究，旨在确定在固定剂量的顺铂与热疗基础上联合拉帕替尼的最大耐受剂量（MTD）。 方法 . 共纳入8例既往接受过照射治疗的复发子宫颈癌患者，计划给予顺铂70 mg/m 2 联合局部热疗，每周1次，共6周。热疗要求腔内尽可能均匀加热至40 ∼ 43°C，持续> 60分钟。在第1 ∼ 56天，每天给予一次拉帕替尼治疗，起始剂量为1 000 mg。MTD定义为≤ 1/6例患者发生剂量限制性毒性（DLT）事件的最大剂量。DLT定义为4级中性粒细胞减少持续> 7天、≥ 3级发热性中性粒细胞减少、4级血小板减少、≥ 2级肾毒性、顺铂和热疗推迟≥ 2周，或者发生≥ 3级非血液学毒性事件（除外恶心、呕吐或皮肤毒性）；对于恶心、呕吐或皮肤毒性，则适用下述DLT定义：尽管给予最佳药物治疗，仍然发生≥ 3级持续性恶心或呕吐或腹泻，或4级皮肤毒性。研究还评估了安全性、药效学和缓解情况。 结果 . 最初2例患者在1 000 mg和750 mg剂量水平均发生了DLT。4例患者接受了下降2级剂量水平（500 mg）的药物治疗，其中仅1例按计划完成治疗，2例患者发生了DLT，1例患者因疾病早期进展而无法评价。在可评价患者中，1例疾病进展，4例疾病稳定，2例部分缓解。1例部分缓解的患者接受了局部复发病灶切除术。病理学分析提示完全缓解。基线和治疗期间循环内皮细胞计数显示结果不一致；同样的，治疗前和治疗期间皮肤活检提示治疗对Ki‐67、p27Kip1和EGFR的药效学作用结果也不一致。 结论 . 在既往照射野内复发子宫颈癌患者中，给予固定剂量顺铂和热疗联合拉帕替尼治疗不可行，主要是由于顺铂相关的毒性事件增加。但我们观察到的病理学完全缓解很有意义，值得开展进一步的研究，对含HER2阻滞剂和顺铂联合热疗的方案进行观察。 The Oncologist 2015;20:241–242